2023
DOI: 10.1021/acs.nanolett.3c04128
|View full text |Cite
|
Sign up to set email alerts
|

Li Salt Assisted Highly Flexible Carbonaceous Ni3N@polyimide Electrode for an Efficient Asymmetric Supercapacitor

Ravikant Adalati,
Siddharth Sharma,
Meenakshi Sharma
et al.

Abstract: This work used a highly flexible, sustainable polyimide tape as a substrate to deposit ductile-natured carbonaceous Ni 3 N (C/Ni 3 N@polyimide) material for supercapacitor application. C/Ni 3 N was prepared using a co-sputtering technique, and this method also provided better adhesion of the electrode material over the substrate, which is helpful in improving bending performance. The ductile behavior of the sputter-grown electrode and the high flexibility of the polyimide tape provide ultimate flexibility to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
0
0
0
Order By: Relevance
“…The areal capacitance calculated from the CV and GCD curves are tabulated in Tables S8 and S9. Figure f displays the Ragone plot illustrating the trend of energy density vs power density of WSe 2 @graphite SS in comparison with the previously reported literature data. It is observed that the fabricated SS exhibits a high energy density of 5.54 mWh cm –2 at a power density of 120 mW cm –2 , higher than those of various previously reported TMDCs and other devices. In the present work, WSe 2 thin-film nanoflakes are fabricated over a graphite substrate by using the binder-free, low-cost, and eco-friendly DC magnetron sputtering approach.…”
Section: Resultsmentioning
confidence: 59%
“…The areal capacitance calculated from the CV and GCD curves are tabulated in Tables S8 and S9. Figure f displays the Ragone plot illustrating the trend of energy density vs power density of WSe 2 @graphite SS in comparison with the previously reported literature data. It is observed that the fabricated SS exhibits a high energy density of 5.54 mWh cm –2 at a power density of 120 mW cm –2 , higher than those of various previously reported TMDCs and other devices. In the present work, WSe 2 thin-film nanoflakes are fabricated over a graphite substrate by using the binder-free, low-cost, and eco-friendly DC magnetron sputtering approach.…”
Section: Resultsmentioning
confidence: 59%